Дослідження рівня безпеки та оцінка ризиків роботів для особистого догляду - Цимбал, Б. М.; Свіржевський, П. В. (Харківський національний університет міського господарства імені О.М. Бекетова, 2025)
Було досліджено рівень безпеки, виконано оцінку ризиків роботів для особистого догляду та надано рекомендації щодо усунення та/або зменшення ризиків. Під час дослідження було встановлено, що роботи для особистого догляду не зважаючи на свою соціальну функцію під час експлуатації та контакті з людиною є небезпечними і призводять до травматизму.

This study investigates the safety levels and risk assessment of personal care robots, focusing on their interaction with users and potential hazards. The increasing use of autonomous robots in personal care, particularly for elderly individuals, presents significant safety concerns. Although these robots are designed to assist users in daily activities, they pose risks such as mechanical injuries, electrical malfunctions, and privacy violations. Additionally, ethical concerns regarding user dependency and psychological effects are becoming increasingly relevant.
Safety level research and risk assessment of personal care works
Keywords: безпечна експлуатація; заходи з безпеки; роботи для особистого догляду; оцінка ризиків; safe operation; safety measures; personal care work; risk assessment